What do physicians want at the end? An international qualitative study on physicians’ personal end-of-life preferences and what influences them - Sarah Mroz; Frederick Daenen; Sigrid Dierickx; Freddy Mortier; Ludovica De Panfilis; Luca Ghirotto; Toby Campbell; Kenneth Chambaere; Luc Deliens (Palliative Care and Social Practice, 2025)
Background: Physicians play a key role in end-of-life decision-making. As research suggests a connection between physicians’ personal end-of-life preferences and their clinical practice, it is important to understand what physicians want for themselves at the end of life and what has shaped their preferences. Objective: To explore what physicians have considered for their end-of-life preferences, including life-sustaining and life-shortening practices, and their perceptions of the socio-cultural factors that influence their preferences. Design: Qualitative study using in-depth interviews. Methods: Forty-five interviews were conducted from January to November 2022 using a semi-structured interview guide. Participants included three types of physicians: general practitioners, palliative care physicians, and other medical specialists in Belgium (Flanders), Italy, and the United States (Wisconsin). Data collection and analysis were informed using the reflexive thematic analysis approach. Audio recordings were transcribed verbatim and NVivo 14 was used for coding and analysis. Consolidated criteria for reporting qualitative research (COREQ) were followed. Results: We found physicians, particularly those in palliative care, have reflected on their end-of-life preferences and have ideas about what constitutes a good death and what they hope to avoid. Most physicians prefer to avoid aggressive and life-prolonging treatment, physical and mental suffering, and being a burden. They prioritize being in a peaceful environment and communication with loved ones. Various factors influence preferences including cultural, social, and religious beliefs, and legislative environment, but most significant are the deaths of loved ones and clinical practice. Death and dying become normalized the more they are reflected upon and discussed, and this process can also provide personal growth which helps physicians provide better care to patients and families. Conclusion: Physicians have reflected on their end-of-life preferences and prefer a peaceful end of life without aggressive and life-prolonging treatment. Physicians’ views on end-of-life practices are influenced by evolving cultural and societal norms and legal and ethical factors.